Inherited bowel cancer: a review from a surgeon’s perspective - Saeed, Mirza Faraz; Ebrahim, Basel Maher; Khairi, Sara Salah; Varkey, Roshan George; Juma, Isam Mazin (International Journal Of Community Medicine And Public Health, 2022)
Colorectal cancer (CRC) is the second most deadly cancer affecting globally. Although most CRCs seen in young adults are sporadic, hereditary cancer syndromes should be considered as an essential factor. Screening for colorectal cancer aids in the early detection and treatment of early-stage CRC; which reduces mortality rates. This review article aimed to present neoplastic and non-neoplastic polyps and their management from a surgeon’s perspective while describing screening protocols in high-risk groups. It also highlighted the etiology, clinical features, diagnosis and management of adenomatous polyps and hereditary bowel cancer syndromes like Peutz-Jeghers syndrome (PJS), juvenile polyposis syndrome (JPS), Cowden syndrome (CS), Lynch syndrome (LS) and familial adenomatous polyposis (FAP). The article summarized the importance of these syndromes as a risk factor in colorectal cancer and identifies these as high-risk group patients in colorectal screening protocols. A summary of the management of these risk factors has been described from a surgeon’s point of view.